Detection of an Explosive Outflow in G34.26+0.15 - Namitha Issac; Xing Lu; Tie Liu; Luis A. Zapata; Hong-Li Liu; Anandmayee Tej; Yan-Kun Zhang; Wenyu Jiao; Suinan Zhang (The Astronomical Journal)
This paper reports on the detection of a likely explosive outflow in the high-mass star-forming complex G34.26+0.15, adding to the small number (six) of explosive outflows detected so far. ALMA CO(2–1) and SiO(5–4) archival observations reveal multiple outflow streamers from G34.26+0.15, which correlate well with H _2 jets identified from Spitzer-IRAC 4.5 μ m and [4.5]/[3.6] flux ratio maps. These nearly linear outflow streamers originate from a common center within an ultracompact H ii region located in the complex. The velocity spread of the outflow streamers ranges from 0 to 120 km s ^−1 . The radial velocities of these streamers follow the Hubble–Lemaître velocity law, indicating an explosive nature. From the CO emission, the total outflow mass, momentum, and outflow energy are estimated to be ∼264 M _⊙ , 4.3 × 10 ^3 M _⊙ km s ^−1 , and 10 ^48 erg, respectively. The event triggering the outflow may have occurred about 19,000 yr ago and could also be responsible for powering the expanding UC H ii region, given the similar dynamical ages and positional coincidence of the UC H ii region with the origin of the outflow. The magnetic field lines in the region associated with G34.26+0.15 also appear to align with the direction of the outflow streamers and jets, possibly being dragged by the explosive outflow.